Low Pretreatment Viral Loads in Infants With HIV in an Era of High-maternal Antiretroviral Therapy Coverage. Issue 1 (January 2021) - Patel, Faeezah; Shiau, Stephanie; Strehlau, Renate; Shen, Yanhan; Burke, Megan; Paximadis, Maria; Shalekoff, Sharon; Schramm, Diana; Technau, Karl-Günter; Sherman, Gayle G.; Coovadia, Ashraf; Tiemessen, Caroline T.; et al.
Abstract : Background: With expansion of antiretroviral therapy (ART) programs, transmission rates are low but new infant infections still occur. We investigated predictors of pre-ART viral load (VL) and CD4+ T-cell counts and percentages in infants diagnosed with HIV at birth in a setting with high coverage of maternal ART and infant prophylaxis. Methods: As part of an early treatment study, 97 infants with confirmed HIV-infection were identified at a hospital in Johannesburg, South Africa. Infant VL and CD4+ T-cell parameters were measured before ART initiation. Data were collected on maternal characteristics, including VL, CD4+ T-cell counts and ART, and infant characteristics, including sex, birth weight, and mode of delivery. Results: Pre-ART, median infant VL was 28, 405 copies/mL [interquartile range (IQR): 2515–218, 150], CD4+ T-cell count 1914 cells/mm 3 (IQR: 1474–2639) and percentage 40.8% (IQR: 32.2–51.2). Most (80.4%) infants were born to mothers who received ART during pregnancy and 97.9% of infants received daily nevirapine prophylaxis until ART initiation at median of 2 days of age (IQR: 1−7). Infant pre-ART VL was more likely to be ≥1000 copies/mL when their mothers had VL ≥1000 copies/mL [Odds Ratio (OR): 6.88, 95% confidence interval (CI): 2.32–20.41] and was higher in boys than girls (OR: 3.29, 95% CI: 1.07–9.95). Lower maternal CD4+ T-cell count (<350 cells/mm 3 ) was associated with lower infant CD4+ T-cell count (<1500 cells/mm 3 ) (OR: 3.59, 95% CI: 1.24–10.43). Conclusions: Pre-ART VL and CD4+ T-cell parameters of intrauterine-infected infants were associated with VL and CD4+ T-cell counts of their mothers. Maternal ART during pregnancy may begin treatment of intrauterine infection and may mask the severity of disease in infected infants identified in the current era with high-maternal ART coverage. Abstract : Supplemental Digital Content is available in the text.